2020
DOI: 10.1007/s00204-020-02775-6
|View full text |Cite
|
Sign up to set email alerts
|

The cyanobacterial neurotoxin β-N-methylamino-l-alanine (BMAA) targets the olfactory bulb region

Abstract: Olfactory dysfunction is implicated in neurodegenerative disorders and typically manifests years before other symptoms. The cyanobacterial neurotoxin β-N-methylamino-l-alanine (BMAA) is suggested as a risk factor for neurodegenerative disease. Detection of BMAA in air filters has increased the concern that aerosolization may lead to human BMAA exposure through the air. The aim of this study was to determine if BMAA targets the olfactory system. Autoradiographic imaging showed a distinct localization of radioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Although this field is vast, one area of interest involves the naturally occurring bacterial toxin ß-N-methylamino-L-alanine (BMAA). Occasionally found in dangerously toxic concentrations within certain seafood, BMAA consumption has been shown to cause a significant shift in the microbial environment of the gut [ 122 , 123 ], demonstrating to have profound effects on the propagation of αSyn from the gut to the brain and the subsequent development of PD [ 122 , 124 ]. Interestingly, BMAA has causal links to both ALS and PD, being the key contributor to the rare incidence of the ALS-PD complex in the western Pacific islands of Guam and Japan [ 125 , 126 ].…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Although this field is vast, one area of interest involves the naturally occurring bacterial toxin ß-N-methylamino-L-alanine (BMAA). Occasionally found in dangerously toxic concentrations within certain seafood, BMAA consumption has been shown to cause a significant shift in the microbial environment of the gut [ 122 , 123 ], demonstrating to have profound effects on the propagation of αSyn from the gut to the brain and the subsequent development of PD [ 122 , 124 ]. Interestingly, BMAA has causal links to both ALS and PD, being the key contributor to the rare incidence of the ALS-PD complex in the western Pacific islands of Guam and Japan [ 125 , 126 ].…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…While the toxic effects of BMAA have been primarily reported via ingestion, emerging studies suggest that inhalation exposure may also provide risks for neurological illness [26] , [27] , [28] . This hypothesis is supported by animal models showing that intranasal administration of BMAA can transfer directly to and concentrate in the olfactory bulb ( Ob ) [29] . Direct application of the toxin to olfactory cells causes cell cycle arrest, excitotoxicity, reduced viability with cell death, and decreased mitochondrial function [29] , [30] , [31] , [32] .…”
Section: Introductionmentioning
confidence: 86%
“…This hypothesis is supported by animal models showing that intranasal administration of BMAA can transfer directly to and concentrate in the olfactory bulb ( Ob ) [29] . Direct application of the toxin to olfactory cells causes cell cycle arrest, excitotoxicity, reduced viability with cell death, and decreased mitochondrial function [29] , [30] , [31] , [32] . However, studies regarding BMAA exposures involving the human respiratory tract are still emerging [14] .…”
Section: Introductionmentioning
confidence: 86%
“…Chernoff et al (2017) argue that previous studies do not facilitate determination of environmental BMAA concentrations that are dangerous to human health. The oral route is likely the primary way of BMAA exposure although recent studies have revealed that BMAA also can be transferred to the brain via the olfactory pathways (Pierozan et al 2020).…”
Section: Animal Studies and Environmental Exposuresmentioning
confidence: 99%
“…Misincorporation of BMAA is only one of many mechanisms acknowledged as possibly contributing to triggering sporadic neurodegenerative diseases (Chiu et al 2011;Arif et al 2014) and for examples since 2017 see (Beri et al 2017;Metcalf et al 2017;D'Mello et al 2017;Potjewyd et al 2017;Powers et al 2017;Engskog et al 2017;Michaelson et al 2017;Díaz-Parra et al 2017;Tan et al 2018a, b;Downing 2018, 2019;Albano and Lobner 2018;Main and Rodgers 2018;Laugeray et al 2018;Lepoutre et al 2018;Pierozan et al 2018Pierozan et al , 2020Gerić et al 2019;Cheng et al 2019;Pierozan and Karlsson 2019;Tedeschi et al 2019;Diaz-parga et al 2020;Li et al 2020;Ndaru et al 2020;Vallerga et al 2020). Chernoff et al (2017) presents multiple lines of evidence to refute that L-BMAA is a substrate for protein incorporation and we address these below.…”
Section: Misincorporation Of Bmaa Into Proteinsmentioning
confidence: 99%